Comparative analysis of different hepatico-jejunostomy techniques for treating adult type I choledochal cyst. (2nd July 2017) - Ma, Wenjie; Tan, Yongqiong; Shrestha, Anuj; Li, Fuyu; Zhou, Rongxing; Wang, Junke; Hu, Haijie; Yang, Qin
Abstract: Objective: To compare Roux-en-Y hepatico-jejunostomy with complete resection of the cyst or incomplete resection with 1-cm remnant proximal cyst wall in treating adult type I choledochal cyst (CC). Methods: The medical records of 267 adult patients with type I CC from January 1998 to December 2015 were reviewed retrospectively. Among them, 171 underwent Roux-en-Y hepatico-jejunostomy with complete resection (PBD 0-cm group) and 96 underwent Roux-en-Y hepatico-jejunostomy with 1-cm proximal cyst wall left (PBD 1-cm group). The short- and long-term post-operative complications were compared between the two groups. Results: No significant difference was observed in operative time or anastomotic diameter between the two groups. The incidence of perioperative complications was significantly higher in the PBD 1-cm group than that in the PBD 0-cm group (28.1% vs 14.0%, p =0.005), especially post-operative cholangitis (7.3% vs 1.2%, p =0.021). The incidence of long-term post-operative complications was not significantly different, including anastomotic stricture, reflux cholangitis, intra-hepatic bile duct stones and bile leak (all p >0.05). Post-operative intra-pancreatic biliary malignancy occurred in one patient in the PBD 0-cm group at 25 months and one patient in the PBD 1-cm group at 5 month, respectively. Anatomical site malignancy was observed in one patient in the PBD 1-cm group at 10 months. Conclusion: Ease of performing anastomosis does not justify retaining a segment of choledochal cyst in type I CC due to its higher risk of post-operative complication and malignancy. A complete excision of the CC with anastomosis to the healthy proximal bile duct is necessary in treatment of type I CC.